2009
DOI: 10.1161/circep.108.817205
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of the Radiofrequency Hot Balloon Catheter for Isolation of the Posterior Left Atrium and Pulmonary Veins for the Treatment of Atrial Fibrillation

Abstract: Background-Atrial fibrillation originates mostly from the pulmonary vein (PV) foci or non-PV foci in the posterior left atrium (LA). The present study was designed to evaluate the feasibility and safety of a novel radiofrequency hot balloon catheter for the treatment of patients with atrial fibrillation by electrically isolating the posterior LA, including all PVs. Methods and Results-One hundred consecutive patients with drug-resistant atrial fibrillation (63 paroxysmal, 37 persistent) were enrolled. The isol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
74
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(79 citation statements)
references
References 25 publications
4
74
0
1
Order By: Relevance
“…706 A central electrode delivers RF energy to the saline in the balloon, and a unique mixing system creates turbulent flow, promoting uniform distribution of the heated saline throughout the balloon. The balloon surface directly heats the PV wall circumferentially.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…706 A central electrode delivers RF energy to the saline in the balloon, and a unique mixing system creates turbulent flow, promoting uniform distribution of the heated saline throughout the balloon. The balloon surface directly heats the PV wall circumferentially.…”
Section: Section 6: Technology and Toolsmentioning
confidence: 99%
“…[3] The independent predictor of AF recurrence was heart failure with preserved ejection fraction (EF). [4,5] In a previous study, [4] 92 patients were free from AF (60 paroxysmal, 32 persistent), but cases with severe heart failure and a dilated left atrium (> 55 mm) were excluded. However, in the present case, the patient developed decompensated heart failure with severe LV dysfunction, and hot balloon ablation was effective for congestive heart failure with a giant left atrium.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been reported that the time of isolation can be shorter with balloon ablation than with CA; [1,2] therefore, the intravenous drip volume is small. [3][4][5] We decided to use the balloon technique for a patient with LA dilatation and severe LV dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…23 More anecdotal is the use of the RF hot balloon catheter (Hayama Arrhythmia Institute, Kanagawa, Japan) based on RF delivery between a coil electrode inside the balloon and the four cutaneous electrode patches on the patient's back to induce capacitive-type heating of the balloon. 39,40 The technique allows isolation of the PV and posterior left atrium. No major collateral complications have been reported and the incidence of transient right phrenic nerve palsy was only 1 % in the largest series to date.…”
Section: Single-shot Devicesmentioning
confidence: 99%
“…No major collateral complications have been reported and the incidence of transient right phrenic nerve palsy was only 1 % in the largest series to date. 40 However, the lack of multicentre studies and limited follow-up do not allow to fully evaluate the efficacy of the RF hot balloon catheter for the treatment of AF.…”
Section: Single-shot Devicesmentioning
confidence: 99%